THE EFFECT OF BOGGLE GAME ON STUDENTS’ VOCABULARY IN READING SKILL OF EIGHTH GRADE STUDENTS - Kamiliyatun Nabila. S; Moh. Arief Wahyudi (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
The limited lexical mastery of students that triggers obstacles in recognizing the meaning of words and understanding the contents of instructional texts comprehensively is the background to this research activity. These operational problems trigger low literacy achievement scores, class passivity, and lack of student confidence when instructed to read drafts of foreign language texts. The main focus of this scientific study is to analyze the magnitude of the effect of using the interactive game Boggle Game on the escalation of vocabulary competence in reading skills. The steps of the quasi-experimental quantitative approach with a one-group pre-test and post-test design were operated on a sample of 25 active respondents of grade eight E at SMP Negeri 1 Sepulu. The primary data collection procedure was collected in a structured manner via an initial ability test instrument, a participant observation sheet, and a final evaluation test, which was then executed statistically using Paired Samples T-Test analysis assisted by SPSS software version 32. The quantitative data empirically revealed a jump in the average score from the initial score of 47.60 to 85.20 in the final results, with a significance parameter of p less than 0.001. The main conclusion confirms that the digitalization of word formation mechanics has proven highly effective in boosting long-term memory retention and academic resilience in students. Vocational teachers are recommended to consistently integrate educational game drafts. ABSTRAK Keterbatasan penguasaan leksikal siswa yang memicu hambatan dalam mengenali makna kata serta memahami isi teks instruksional secara komprehensif melatarbelakangi kegiatan penelitian ini. Masalah operasional tersebut memicu rendahnya nilai capaian literasi, pasivitas kelas, serta minimnya rasa percaya diri siswa saat diinstruksikan membaca draf teks berbahasa asing. Fokus utama kajian ilmiah ini adalah menganalisis besaran pengaruh penggunaan permainan interaktif Boggle Game terhadap eskalasi kompetensi kosakata dalam keterampilan membaca (reading skill). Langkah-langkah pendekatan kuantitatif kuasi eksperimen dengan desain one-group pre-test and post-test ini dioperasikan pada sampel sejumlah 25 responden aktif kelas delapan E di SMP Negeri 1 Sepulu. Prosedur pengumpulan data primer dihimpun secara terstruktur via instrumen tes kemampuan awal, lembar observasi partisipasi, serta tes evaluasi akhir, yang selanjutnya dieksekusi statistik menggunakan analisis Paired Samples T-Test berbantuan perangkat lunak SPSS versi 32. Data kuantitatif secara empiris menyingkap adanya lompatan perolehan nilai rerata dari skor awal sebesar 47,60 menjadi 85,20 pada hasil akhir, dengan parameter signifikansi p kurang dari 0,001. Simpulan utama menegaskan bahwa digitalisasi mekanik penyusunan kata terbukti sangat andal dalam mendongkrak retensi memori jangka panjang serta ketahanan akademik siswa. Guru kejuruan direkomendasikan mengintegrasikan draf permainan edukatif secara konsisten.